Extracellular ATP acts as a damage-associated molecular pattern (DAMP) signal in plants - Tanaka, Kiwamu; Choi, Jeongmin; Cao, Yangrong; Stacey, Gary (Frontiers in Plant Science, 2014)
As sessile organisms, plants have evolved effective mechanisms to protect themselves from environmental stresses. Damaged (i.e., wounded) plants recognize a variety of endogenous molecules as danger signals, referred to as damage-associated molecular patterns (DAMPs). ATP is among the molecules that are released by cell damage, and recent evidence suggests that ATP can serve as a DAMP. Although little studied in plants, extracellular ATP is well known for its signaling role in animals, including acting as a DAMP during the inflammatory response and wound healing. If ATP acts outside the cell, then it is reasonable to expect that it is recognized by a plasma membrane-localized receptor. Recently, DORN1, a lectin receptor kinase, was shown to recognize extracellular ATP in Arabidopsis. DORN1 is the founding member of a new purinoceptor subfamily, P2K (P2 receptor Kinase), which is plant-specific. P2K1 (DORN1) is required for ATP-induced cellular responses (e.g., cytosolic Ca2+ elevation, MAPK phosphorylation, and gene expression). Genetic analysis of loss-of-function mutants and overexpression lines showed that P2K1 participates in the plant wound response, consistent with the role of ATP as a DAMP. In this review, we summarize past research on the roles and mechanisms of extracellular ATP signaling in plants, and discuss the direction of the future research of extracellular ATP as a DAMP signal.